(untitled) (Journal of the College of Basic Education, 2022)
The concept of borrowing means the concept of experience that is gradually gained by the designer from previous experiences and experiences that work on formulating the following experiences and his successive formations that assist the industrial designer in the process of borrowing his symbols and design forms that could not be included in the core of his visual discourse had it not been for his life and social experience that the designer enjoys. In its design formations, the pragmatic philosophical thought emphasized the role of sensory data as well as observation and remembrance in formulating the metaphorical perception, due to the accumulation of experience, experimentation, and the continuous interaction between the designer and nature.